Natural organic polymers in sustainable health technologies - Serén, Jasmine (My University, 2025)
Sustainability concerns within health technology and healthcare sector have increased in the past few years as climate change and environmental degradation have continued to occur at an expedited speed. Healthcare services on their own account for 4.4% of the global net greenhouse gas (GHG) emissions which makes them a prominent category within global GHG emissions assessments reports. One of the key ways to influence the GHG emissions of health technologies utilized in healthcare services, is to make adjustments in what materials are preferred for the manufacturing of health technology products, such as health monitoring devices. Collagen, chitosan and alginate offer a variety of options for material sourcing from currently existing industries such as fishing, meat or leather. The previously mentioned industries often discard processing waste and by-products such as bones, shells, skin and guts which could be utilized to produce high-value biomass for health monitoring application purposes. It's important to examine sustainable material sourcing from the perspective of material safety, availability as well as environmental and social impact. Among the three chosen materials for this thesis, bovine-derived collagen is the most commonly utilized material due to its long research history, abundance of raw materials as well as favorable properties including biocompatibility and low immunogenicity. Few of the key hinderances for bovine-derived collagen are the risks for zoonosis diseases, population intolerances, and dependency on cattle for raw materials as well as religious concerns. Marine-derived collagen represents a promising alternative to bovine-derived collagen as it is considered to be safer due to lowered risks of transmissible diseases, and it offers an opportunity to valorize previously underutilized fish waste. When considering marine-derived collagen and crustacean-derived chitosan, it’s important to note that overfishing is one of the main material concerns. Insect and fungi derived chitosan offer fast material renewability and superior material properties such as antimicrobial activity and lowered risks of allergic reactions when compared to traditional crustacean-derived chitosan. While collagen and chitosan are most often derived from animal sources, alginate is mainly acquired from brown algae. Alginate sourced from brown algae exhibits good non-immunogenicity, non-toxicity and biocompatibility properties and presents a beneficial way to decrease pressure on land resources as well as to applying traditional cultural knowledge from coastal areas.

Kestävyys kysymykset terveysteknologian ja terveydenhuollon sektorilla ovat lisääntyneet viime vuosien aikana, sillä ilmaston muutos sekä luonnon heikkeneminen tapahtuu kiihtyvässä vauhdissa. Terveydenhuollon palvelut itsessään tuottavat 4,4 % maailman netto kasvihuonekaasupäästöistä, minkä takia sektori on erottuva kategoria maailmanlaajuisissa kasvihuonepäästöjen arviointiraporteissa. Yksi keskeisistä tavoista vaikuttaa terveysteknologiasta aiheutuviin päästöihin terveydenhuollossa, on tekemällä muutoksia siihen mitä materiaaleja suositaan terveysteknologian tuotteiden, kuten monitorointilaitteiden, tuotannossa. Kollageeni, kitosaani ja alginaatti tarjoavat laajat mahdollisuudet materiaalien hankintaan olemassa olevista teollisuuden aloista, kuten kalastuksesta, lihatuotannosta sekä nahkateollisuudesta. Edellä mainitut teollisuuden alat tuottavat nykyiseltään sellaista jätettä ja sivutuotteita, kuten luut, äyriäisten kuoret, nahka ja sisäelämiä, joita voitaisiin hyödyntää korkealaatuisen biomassan tuottamiseen terveysteknologian tarpeisiin. On tärkeää tarkastella kestävää materiaalihankintaa materiaaliturvallisuuden, saatavuuden sekä ympäristö- ja sosiaalisten vaikutusten kannalta. Diplomityössä käsitellyistä materiaaleista, nautaperäinen kollageeni on yleisimmän käytetty materiaali sen pitkän tutkimushistorian, raaka-aineiden runsauden sekä suotuisten ominaisuuksien kuten bioyhteensopivuuden sekä immunogeenisyyden vuoksi. Keskeisimpiä ongelmia nautaperäisessä kollageenissa ovat riski zoonoosi tautien leviämisestä, väestön intoleranssit, raaka-aine riippuvuus lihatuotannosta sekä uskonnolliset syyt. Meriperäinen kollageeni tarjoaa lupaavan vaihtoehdon perinteiselle nautaperäiselle kollageenille, sillä sitä luonnehditaan turvallisemmaksi materiaaliksi alhaisemman zoonoosi tauti riskien vuoksi ja meriperäinen kollageeni tarjoaa mahdollisuuden hyödyntää aiemmin alihyödynnettyä kalajätettä. Tarkasteltaessa meriperäisen kollageenin sekä äyriäisistä saatavan kitosaanin materiaalihankintaa, on tärkeää huomioida, että yksi keskeisimmistä ongelmista on riski ylikalastuksesta. Hyönteisistä ja sienistä saatava kitosaani on nopeasti uusiutuva materiaali ja myös materiaalin omaisuudet kuten antimikrobinen toiminta sekä alentunut allergeenisen reaktion riski, ovat paremmat kuin perinteisellä äyriäisistä saatavalla kitosaanilla. Kollageeni ja kitosaani ovat yleensä eläinperäisiä, kun taas alginaatti hankitaan pääsääntöisesti ruskeista levistä. Ruskeista levistä peräisin oleva alginaatti on ei-immunogeeninen, myrkytön ja bioyhteensopiva sekä helpottaa maaresurssien käyttöpainetta ja mahdollistaa rannikkoalueiden perinteisen kulttuuritiedon hyödyntämisen materiaalin valmistukseen.
Keywords: organic polymers, sustainability, health monitoring, collagen, chitosan, alginate, material sourcing